Comparative phylogeography of alpine invertebrates indicates deep lineage diversification and historical refugia in the Australian Alps. (4th August 2014) - Endo, Yoshinori; Nash, Michael; Hoffmann, Ary A.; Slatyer, Rachel; Miller, Adam D.; Parmakelis, Aristeidis
Abstract Aim Comparative phylogeographic analyses of alpine biota from the Northern Hemisphere have linked patterns of genetic diversification to glacial expansion and contraction events in the Pliocene and Pleistocene. Furthermore, the extent of diversification across species groups appears to be associated with vagility. In this study we test whether these patterns apply to a geologically stable system from eastern Australia with comparatively shallow elevational gradients and minimal influence from historical glacial activity. Location The Australian Alps, Victoria, eastern Australia. Methods We considered phylogeographic patterns across five alpine invertebrate species based on mitochondrial and nuclear DNA sequence data. Bayesian inference methods were used to estimate species phylogenies and divergence times among lineages. GIS tools were used to map interpopulation genetic divergence and intrapopulation genetic diversity estimates and to visualize spatial patterns across species, providing insights into patterns of endemism and demographic history. Results Phylogeographic patterns and the timing of lineage diversification were consistent across taxonomic groups. Mountain summits harbour highly differentiated haplogroups, including summits connected by high‐elevational plateaus, pointing to diversifications being maintained since the early to mid‐Pleistocene. These findings are consistent with previous studies of alpine mammals and reptiles, demonstrating a high degree of endemism in this region, regardless of species vagility. Main conclusions The fine spatial scales at which deep genetic differentiation among alpine communities was observed in this study are unprecedented. This suggests that glacial periods have had less of an impact on species distributions and genetic diversity than they have in alpine systems in the Northern Hemisphere. Historical gene flow among sky‐island populations has been limited despite connecting snowlines during glacial periods, suggesting that factors other than snow cover have influenced patterns of gene flow in this region. These findings emphasize the unique phylogeographic history affecting Victorian alpine biodiversity, and the importance of conserving biodiversity from multiple mountain summits in this region of high endemism.